STRATEGI PENGUATAN KEPEMIMPINAN VISIONER, KOMUNITAS BELAJAR DAN EFIKASI KOLEKTIF UNTUK MENIGKATKAN EFEKTIVITAS PEMBELAJARAN - Rukbi, Dasep Ahmad; Hidayat, Nandang; Suharyati, Henny (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Differentiated learning can create a learning environment that is tailored to the needs of each student, especially in an independent curriculum, its implementation is a big challenge. This study aims to find strategies and ways to improve the effectiveness of differentiated learning through strengthening visionary leadership, learning communities, and collective efficacy. The study used the path analysis method and SITOREM analysis with a quantitative approach. This study concluded that visionary leadership, learning communities, and collective efficacy are key factors in improving the effectiveness of differentiated learning. Collective efficacy acts as a mediator in the relationship between visionary leadership and learning communities on the effectiveness of differentiated learning. The application of visionary leadership and learning community strategies supports the improvement of teacher collective efficacy and can help improve the effectiveness of differentiated learning. Keywords : Visionary leadership, learning communities, collective efficacy, differentiated learning